Chlorophytum assamicum (Asparagaceae), a new species from Northeast India - Borah, Dipankar; Kafley, Parixit; Das, Abhaya P.; Tangjang, Sumpam; Averynov, Leonid (Phytotaxa, 2019)
The genus Chlorophytum Ker Gawler (1808: 1071) (Asparagaceae), includes about 200 species (Govaerts et al. 2012) distributed in the Old World tropics (Mabberley 2017). In India, this genus is represented by 19 species (Malpure & Yadav 2009; Chandore et al. 2012), including the new species proposed below. Indian species of Chlorophytum are usually forest dwellers and are cryptophytic with aboveground organs disappearing in the dry season (Chandore et al. 2012). Most of the members of Chlorophytum, reported from India have their distribution in Western Ghats except C. nepalense (Lindley 1826: 277) Baker (1876: 320), C. comosum (Thunberg 1794: 63) Jacques (1862: 345), C. breviscapum Dalzell (1850: 141), and C. arundinaceum Baker (1876: 323) growing in northeastern Himalaya (Adsul 2015).